Decentralized weather monitoring system for smart cities - Sripath Roy, K; Sowmya, S; Manasa, M; Alekhya, D; Abhinav, P (International Journal of Engineering and Technology, 2018)
Internet of things involves monitoring as one of its major applications. It mostly includes condition-based decisions without human intervention. Monitoring systems continuously read the data from sensors, upload the data to a database and take appropriate decisions when they encounter an abnormal data. This provides a good basis for the IoT control systems which now are mostly common. This paper explains the solution to replace the single server system which means a centralized system with an individual server system which is a decentralized system. A decentralized system provides high security to the data and ensures data privacy which centralized systems fail to do. This decentralized system involves maintaining own server but ensuring the availability of data & communication without loss of privacy, ensuring minimization of security threats. This application involves building of a collective application on an android platform to present the data to the users based on the user hierarchy defined. The app provides high security through authentication based on the rights that user possesses. This app is designed to continuously monitor the air pollution in the areas across the city and give alerts or notifications whenever the pollution level reaches to a threshold. Additionally, the app monitors temperature and humidity level. Analytics are performed on the data from sensors and a graph is plotted as the value of a parameter across time. Separate graphs are plotted for each parameter. A user with administrator privilege can view the data of all the areas whereas a user from a single location or a user with general privilege gets the data of his own location.Â